Review on MadhukadiTaila-a SnehaKalpana - SolapurkarVivek V; S. M. Pasha; SujaK Sreedhar (International Journal of Pharmacy and Analytical Research, 2022)
Taila paka is a unique preparation told in Ayurvedic classics. This method of preparation helps in scavenging those active principles present in raw drugs which are lipid soluble. Taila is considered under maha sneha which mainly controls vata, similarly other doshas depending on medicines which are used for taila paka. Madhukadi taila is mentioned in Timira pratishedha adhyaya of Ashtanga Hrudaya by Acharya Vagbhata. This taila mitigates Vataja and Sannipataja timira. This taila if used for nasya will gives better results.